Psychoactive substance user embracement by the multiprofessional team of the Psychosocial Care Center III* - Ana Cristina dos Santos Vangrelino (SMAD, Revista Electrónica en Salud Mental, Alcohol y Drogas, 2018)
The objective of this study was to learn how the multiprofessional team of a Psychosocial Care Center performs psychoactive substance user embracement. Data were collected by participant observation and a semi-structured interview. The categories of analysis were: context of teamwork, anti-relationship with the drug and the relationship with the person. It was concluded that there is distancing of the multiprofessional nursing team, with embracement based on the biomedical model and drug abstinence, and some relation initiatives with the user. The contribution is configured by embracement articulated to relational technology, based on principles such as empathy, guiding attitude, genuineness and congruence, in order to enhance the relationship with the person and minimize the team’s anti-relationship with the drug.